2009
DOI: 10.1094/phyto-99-9-1062
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Genetic Diversity Among ‘Candidatus Liberibacter asiaticus’ Isolates Collected in Southeast Asia

Abstract: The aim of this study was to investigate the genetic diversity and relationships among 'Candidatus Liberibacter asiaticus' isolates from different hosts and distinct geographical areas in Southeast Asia. Genetic diversity among 'Ca. Liberibacter asiaticus' was estimated by sequencing four well-characterized DNA fragments: the 16S ribosomal DNA (rDNA) and 16S/23S intergenic spacer regions; the outer membrane protein (omp) gene region; the trmU-tufB-secE-nusG-rplKAJL-rpoB region (gene cluster region); and the ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 61 publications
(63 citation statements)
references
References 25 publications
2
59
0
2
Order By: Relevance
“…All the isolates sequenced in this study were 3,609 nucleotides long, and were identical among isolates. Moreover, sequence alignment was carried out using the sequences obtained in this study and the previously reported sequences of the Southeast Asian isolates 16 . Interestingly, the nine Japanese isolates sequenced in this study were identical with four Taiwanese isolates (TW2, TW3, TW5, and TW6, data not shown).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…All the isolates sequenced in this study were 3,609 nucleotides long, and were identical among isolates. Moreover, sequence alignment was carried out using the sequences obtained in this study and the previously reported sequences of the Southeast Asian isolates 16 . Interestingly, the nine Japanese isolates sequenced in this study were identical with four Taiwanese isolates (TW2, TW3, TW5, and TW6, data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…Our previous study suggests that the polymorphic DNA pol may be useful for molecular differentiation among the Southeast Asian Las isolates 16 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations